Acute localized exanthematous pustulosis caused by cefoperazone and sodium sulbactam - Yan-Jing Qu; Shu-Bin Jin; Xiang-Chun Han; Li-Qiang Zheng (Sociedade Brasileira de Dermatologia, 2016)
Abstract Acute localized exanthematous pustulosis is a localized variant of acute generalized exanthematous pustulosis, which is characterized by the eruption of multiple scattered pustules following drug administration. A 72-year-old woman presented with multiple erythematous pustules on her face, which had appeared two days after using cefoperazone and sodium sulbactam. Histopathological findings showed subcorneal pustules and mixed inflammatory cell infiltration in the dermis. The pustules resolved within about two weeks after the patient discontinued the antibiotics. This report discusses the case of a woman with a cutaneous drug reaction consistent with acute localized exanthematous pustulosis that occurred after cefoperazone and sodium sulbactam were administered.